Sexuality in childhood: uxtapositions and parataxes about heteronormativity and family - Opolski, Débora; Ribeiro, Everton (Revista Hipótese, 2022)
This article develops a reading about the production of an audiovisual material entitled “Who defends the child?”, created from contemporary debates about childhood and sexuality, especially those proposed by Paul B. Preciado. Considering the issues of cinematic design, the authors explore an argument that involves ethical and aesthetic dimension about the oppressions and gender normativities, mainly those that are present in child development.
Keywords: Sexuality in childwood; Heteronormativity; Family; Parataxe